Flexural behavior of FRP and steel reinforced glulam beams: Experimental and theoretical evaluation. (1st March 2016) - Yang, Huifeng; Liu, Weiqing; Lu, Weidong; Zhu, Shijun; Geng, Qifan
Graphical abstract: Highlights: Four-point bending of FRP and steel reinforced glulam beams. Effects of reinforcing materials and reinforcement ratio on the flexural behavior. Experimental and theoretical evaluation of the reinforced glulam beams. Parametric analysis and its application in predicting failure modes. Abstract: This paper describes an experimental test program and theoretical analysis which examines the reinforcing in flexure of glued laminated timber (glulam) beams using fiber reinforced polymer (FRP) and steel materials. A series of four-point bending tests were conducted till failure on both unreinforced and reinforced Douglas fir glulam beams in a simply-supported scheme. The focus of this research was to evaluate the effects of reinforcing materials, reinforcement ratio and arrangement on the flexural behavior. Test results showed that the flexural capacity, flexural global stiffness and timber tensile strain at failure were all improved considerably for reinforced timber beams when compared to the unreinforced control beams, in which the average improvement reached 56.3%, 27.5% and 49.4%, respectively. On the bases of the experimental results, a theoretical model was proposed to predict the flexural capacity and flexural stiffness of the reinforced timber beams. Most of the differences between theoretical and experimental results for both flexural capacity and flexural stiffness were within 10.0%, which showed a high accuracy of the proposed model. Subsequently a parametric analysis, which includes the axial stiffness ratio of reinforcement to timber, the relative location of tensile reinforcement, and the strength ratio of reinforced timber between flexural tension and compression, was undertaken to investigate the effects of the influential factors for both flexural capacity and flexural stiffness.